2019
DOI: 10.1111/1475-6773.13175
|View full text |Cite
|
Sign up to set email alerts
|

An informed public's views on reducing antibiotic overuse

Abstract: Objective To understand public attitudes about and recommendations to address antibiotic overuse by employing public deliberation (a method for eliciting informed input on value‐laden issues). Data Sources/Study Setting Participants in 24 Community Deliberation groups (CD; n = 263), four Citizens’ Panel groups (CP; n = 96), and a control group (n = 348). Data were collected in 2012 in four U.S. locations. Study Design Using mixed methods, we analyzed quantitative and qualitative data from a randomized control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Patients seemed to have been more prepared to openly deliberate on prescribing decisions and their expectations were more explicit than previously, even though trust in clinician still had a major role to play. 12,19,33 Those participants who emerged as informed patients rejected a blind compliance. Indeed, patient expectations were due to disclosure; for example, it was manifested in the consultations that used 11,19,34,35 Instead of trying to read the patient's mind, prescribers were and must be making the expectations apparent by asking about them.…”
Section: Experience Of Taking Antibioticsmentioning
confidence: 99%
“…Patients seemed to have been more prepared to openly deliberate on prescribing decisions and their expectations were more explicit than previously, even though trust in clinician still had a major role to play. 12,19,33 Those participants who emerged as informed patients rejected a blind compliance. Indeed, patient expectations were due to disclosure; for example, it was manifested in the consultations that used 11,19,34,35 Instead of trying to read the patient's mind, prescribers were and must be making the expectations apparent by asking about them.…”
Section: Experience Of Taking Antibioticsmentioning
confidence: 99%
“…The literature search resulted in 46 statements representing knowledge gaps and misconceptions about antibiotic use. The statements were extracted from a total of 27 publications ( Supplementary File S1 ) [ 6 , 8 , 9 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These statements were divided into four domains: (1) AMR in general, (2) use of antibiotics in general, (3) antibiotics for acute respiratory tract infections, and (4) antibiotics for urinary tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…108 Recently, it has been shown that when informed about individual and social consequences of antibiotic overuse, patients may be more receptive to antibiotic prescription limits. 109 This evidence suggested that the patient role involves staying informed about the issue of antibiotic use and considering potential benefits and harms when making decisions about antibiotic use. We found that informed patients (of antibiotics and the associated risks) displayed more satisfaction with the consultation.…”
Section: Discussionmentioning
confidence: 99%